x+x+x-4-3-2=12

Simple and best practice solution for x+x+x-4-3-2=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+x+x-4-3-2=12 equation:


Simplifying
x + x + x + -4 + -3 + -2 = 12

Reorder the terms:
-4 + -3 + -2 + x + x + x = 12

Combine like terms: -4 + -3 = -7
-7 + -2 + x + x + x = 12

Combine like terms: -7 + -2 = -9
-9 + x + x + x = 12

Combine like terms: x + x = 2x
-9 + 2x + x = 12

Combine like terms: 2x + x = 3x
-9 + 3x = 12

Solving
-9 + 3x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 3x = 12 + 9

Combine like terms: -9 + 9 = 0
0 + 3x = 12 + 9
3x = 12 + 9

Combine like terms: 12 + 9 = 21
3x = 21

Divide each side by '3'.
x = 7

Simplifying
x = 7

See similar equations:

| 6-9x+4y=0 | | 8x-4=48 | | 4(k+1)=16 | | 78=-0909089 | | 32534-57908= | | x+(-8)=6 | | 32534-57908=89 | | 2y-4=8 | | 54x-788767= | | p(x)=x^3-5x^2-17x+21 | | 2y=8x+10 | | 12221-6756-8=67 | | y(y-3)=4 | | 3x^2+x^2-8x+4=0 | | z^2=15-2z | | n+9/3=14 | | 9y+1=45+2y | | 8x^2+6x^2+2x+5x= | | 78=6x | | -7+2(2n-1)=-31-7n | | 5t-17.2=16.3 | | x+7+x=15 | | s=2B+F | | 10=b(2/3) | | (6u+1)-(2u+5)= | | x+7+x= | | p(x)=x^3+7x^2+4x-12 | | 6x+6+15x+15=4 | | 29.1=3.6a+7.5 | | x^2+3x-650=0 | | 2(3x+3)+3(5x+5)=3 | | 15x+11=12x+56 |

Equations solver categories